Informal Learning in Community: The Role of Subjectivity and Intersubjectivity - Barbara Sparks (Adult Education Research Conference, 2000)
This paper, representing a subset of data from a larger study, provides a preliminary social analysis of a specific site of informal learning with welfare mothers in a job readiness program and the role of subjectivity and intersubjectivity in meaning making. As the women came together to talk about their experiences with each other, they were listened to, taken into account, and validated in their past experiences, current circumstances, and feelings; they also had an opportunity to learn from each other thus illuminating informal learning. The informal learning of women on welfare can assist us in understanding how subjugated knowledges are constructed and how we might facilitate learning.